Congenital diaphragmatic hernia in a patient with tetrasomy 9p - Henriques-Coelho, T (2005)
Tetrasomy of the short arm of chromosome 9 constitutes a rare condition resulting, in a well clinically recognized syndrome. in our case, in addition to the characteristic phenotype at birth, the existence of a hernia-type Bochdalek diaphragmatic defect was found. Cylogenetic analysis revealed a nonmosaic case of an isochromosome of the entire short arm of chromosome 9 with no involvement of the heterochromatic region of the long arm: 47, XX, +i (9p). Because chromosome 9 contains several,I gene locus for enzymes and receptors of the retinoid pathway, this case potentially contributes to retinoid hypothesis in the etiology of congenital diaphragmatic hernia.